PENGARUH BREAST CARE TERHADAP PENINGKATAN PRODUKSI ASI IBU MENYUSUI : A SYSTEMATIC LITERATURE REVIEW - Angela Lovendra Naingalis (STIKes CHMK, 2023)
ASI (Breast Milk) is milk produced by the mother and contains all the nutrients needed by the baby for the growth and development needs of the baby. Efforts to overcome problems that cannot be done in postpartum mothers other than oxytocin massage are breast care. Journal searches were carried out electronically using several databases, namely: DOAJ, JMSCR and Google Scholar from 2015-2022. The keywords are breastfeeding mother, breastmilk production, breast care. The research results of selected articles from 5 international journals and 5 national journals concluded that breast care can increase milk production in post partum mothers. Keywords: Post Partum, Oxytocin Massage, Breast Milk Production.